The Iowa breeding bird atlas - Jackson, Laura Spess (Bur oak original., 1996)
"The Iowa Breeding Bird Atlas begins with an extensive introduction to Iowa's landforms, habitats, and the conditions affecting the abundance of species. From 1985 to 1990, 508 people donated 14,654 hours to locate birds in the field. This tremendous amount of work allowed the authors to create detailed accounts of the distribution and life history for each species of breeding bird in the state. Factors affecting each species are presented, and a distribution map and a photograph accompany each species account. Also included are literature citations for further research; although the fieldwork ended in 1990, information through 1995 is included."--Jacket